Copeptin as biomarker for acute ischemic stroke prognosis and revascularization treatment efficacy - Vasile, Antonia Ioana; Tiu, Cristina; Badiu, Corin (Frontiers in Neurology, 2024)
IntroductionPro-arginine vasopressin consists of three peptides: arginine-vasopressin, neurophysin II, and copeptin. AVP is released by the neurohypophysis in response to increased plasma osmolality, decreased blood volume and stress. Copeptin has the advantage of being stable ex vivo and easy to measure. New data show the importance of copeptin in ischemic stroke and its complications.MethodsWe present a literature review that highlights the importance of copeptin as a biological marker for stroke. We searched the Pubmed and Scopus databases for papers with the following keywords: “stroke AND copeptin.” PRISMA criteria were used.ResultsWe identified 332 papers that met the criteria. We excluded analyzed reviews, systematic reviews and meta-analyses. 31 articles resulted. The number of patients included in the analyzed studies varied between 18 and 4,302. Copeptin is a marker that associated with clinical stroke severity, infarct volume, short-term and long-term functionality and mortality and adds prognostic value to the previously used scales. It may reflect the effectiveness of revascularization therapy. Copeptin is a biomarker that can help predict post-stroke complications such as: cerebral edema and hemorrhagic transformation.DiscussionCopeptin is a novel and promising biomarker for evaluating cerebrovascular diseases. Because it is considered a non-specific biomarker, it is not yet used routinely and it cannot replace the clinical examination. However, combined with other clinical or paraclinical parameters, it can increase the accuracy of the diagnosis.